ISOLASI DAN KARAKTERISASI MORFOLOGI KOLONI BAKTERI PADA SALURAN PENCERNAAN IKAN KERAPU (Cephalopholis miniata) DARI PERAIRAN KABUPATEN KLUNGKUNG BALI - oka suyasa (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2020)
Background. the intestine microflora performs a number of functions such as fermenting unused energy substrates, training the immune system, preventing the growth of harmful species, regulating the development of the intestine and producing vitamins.Purpose. to find out the morphology of bacterial colonies in the digestive tract of Chepalopholis miniata from Kusamba Fish Market, Klungkung Regency.Method. the research is a descriptive exploratory observational study. Grouper faeces are planted in Blood Agar and Mac Concey agar then incubated for 24 hours at 37ºC. Pure isolates were observed macroscopically and microscopically.Results. the morphology of the colony is round and white, the edges of the colony are flat and irregular, the elevations are flat and convex. All isolates were gram-positive in the form of round cells (streptococcus and staphylococcus) and stems (bacilli and streptobacilli).Conclusion. Five bacterial isolates were successfully isolated from the digestive tract of the Cephalopholis miniata.